2005
DOI: 10.1097/01.pas.0000165529.78945.dc
|View full text |Cite
|
Sign up to set email alerts
|

Localized Malignant Mesothelioma

Abstract: Localized malignant mesotheliomas are uncommon sharply circumscribed tumors of the serosal membranes with the microscopic appearance of diffuse malignant mesothelioma but without any evidence of diffuse spread. Little is known about their behavior. We report 23 new cases. The mean age at presentation was 63 years, and the sex ratio was approximately 2:1 (male/female). Twenty-one tumors were pleural and 2 were peritoneal. Sixteen tumors reproduced microscopic patterns of diffuse epithelial mesotheliomas, 6 had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
156
5
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(171 citation statements)
references
References 15 publications
8
156
5
2
Order By: Relevance
“…It can arise from either parietal or visceral peritoneum. A solitary circumscribed peritoneal nodule/mass (as in the present cases) is termed Blocalized^MPM, which is rarer than the Bdiffuset ype but has a much better prognosis because the tumor can be easily resected [10]. However, in the setting of extensive metastasis (as in the present cases), a curative aim of treatment is not possible.…”
Section: Discussionmentioning
confidence: 79%
“…It can arise from either parietal or visceral peritoneum. A solitary circumscribed peritoneal nodule/mass (as in the present cases) is termed Blocalized^MPM, which is rarer than the Bdiffuset ype but has a much better prognosis because the tumor can be easily resected [10]. However, in the setting of extensive metastasis (as in the present cases), a curative aim of treatment is not possible.…”
Section: Discussionmentioning
confidence: 79%
“…[1,9] Resection is considered the treatment of choice for LMM of the pleura. Allen et al [6] reported that almost half of the patients (10 out of 21) were alive after resection 18 months to 11 years after the diagnosis. On the other hand, the other half (n=11) died due to local recurrences and metastases.…”
Section: Discussionmentioning
confidence: 99%
“…[1,3,[7][8][9] Although the role of asbestos exposure in the development of DMM has been described in many reports, a history of asbestos exposure has been detected in only a small proportion of patients with LMM. [4,6,7] Our patient had no known history of asbestos exposure. The clinical presentation of patients is mostly insignificant, and they are generally asymptomatic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most reported cases of localized MM have developed in the pleura or as intrapulmonary or mediastinal tumors, but peritoneal localization and even hepatic and pancreatic tumors with visceral peritoneal origin have also been reported. 3,[74][75][76][77] All histologic subtypes and different morphologic patterns of MM have been described in association with localized MM. Localized MM has a better prognosis than diffuse MM because it is often surgically treatable.…”
Section: Localized MMmentioning
confidence: 99%